Literature review and database on ecosystem service valuation studies for Kenya and Vietnam - Hettiarachchi, Upeksha; Zhang, Wei (International Food Policy Research Institute, 2022)
This review aimed to compile a database of values for ecosystem services in Kenya and Vietnam. The search period for literature was from July 15 to September 15, 2022. The Scopus database and the Ecosystem Services Valuation database were used to identify relevant papers. A total of 162 papers are in the database, with 76 papers about Kenya and 86 about Vietnam. There are 1573 values in the database, 784 for Kenya and 789 for Vietnam. The data collected from each paper in the database included the type of biome, ecosystem service, raw data for the ecosystem service value and the method of ecosystem service value estimation. The variables for which data was collected were based on The Economics of Ecosystems and Biodiversity (TEEB) framework. The TEEB framework allows for the categorization of biomes, sub biomes and types of ecosystem services to be standardized. The ecosystem services are divided into three levels of classification: ecosystem services, ecosystem sub-services and ecosystem sub-sub-services.